The Child’s Right to Development in the Digital Age - Samardžić, Sandra; Gordana Kovaček Stanić, Gordana Kovaček Stanić (Children’s Rights in the Sustainable and Digital Environments: Exploring Opportunities and Challenges, 2025)
Interestingly, the UN Convention on the Rights of the Child and the Internet emerged almost at the same time. However, the process of finalizing the Convention took a long time, and even today, some children's rights are still not fully protected. On the other hand, from the moment the Internet began to represent a social reality, its development proceeded at an incredible speed, overcoming any obstacle, subtly infiltrating almost every sphere of today's human life. Although it may not seem so, the unstoppable development of the digital world was still made possible by humans – those same humans who did not sufficiently focus on the proper development of the child. It is of utmost importance that children's rights, including the right to development, be monitored and protected in all circumstances, including in the digital environment, even if this requires the imposition of certain limitations.